EPIDEMIC ALARMS : SYSTEM CALLS SECURITY HEALTH UKRAINE - Чернишов, Олег; Дробот, Вікторія (SWorldJournal, 2025)
The article investigates the prevalence of anxiety disorders among the Ukrainian population during the full-scale war and the resulting systemic challenges to the mental healthcare sector. The relevance of the study stems from the increasing number of ind